MENGENAL UNSUR DAN JENIS TINDAK PIDANA KORUPSI DI INDONESIA - Triadi, Triadi (Ensiklopedia of Journal, 2024)
The term corruption comes from the Latin words "corruptio" "corruption" (English) and "corruptie" (Dutch), the literal meaning of which refers to actions that are damaged, rotten, dishonest, which are associated with finances. In Black's Law Dictionary, corruption is an act carried out with the intention of providing an informal advantage to other parties, wrongfully using their position or character to obtain an advantage for themselves or others, contrary to their obligations and the rights of those parties. other parties. Based on Law Number 31 of 1999 concerning the Eradication of Corruption Crimes which was amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes, Article 2 and Article 3 define corruption as follows: 1) Any person who intentionally violates the law, commits acts of enriching himself or another person or a corporation which can harm state finances or the state economy; and 2) Any person who, with the aim of benefiting himself or another person or a corporation, abuses the authority, opportunity or means available to him because of his position or position which could harm the state's finances or economy.